Cardiovascular effects of antimuscarinic agents and beta3-adrenergic receptor agonist for the treatment of overactive bladder. Issue 5 (4th May 2018) - Rosa, Gian Marco; Baccino, Danilo; Valbusa, Alberto; Scala, Carolina; Barra, Fabio; Brunelli, Claudio; Ferrero, Simone
ABSTRACT: Introduction : Overactive bladder (OAB) syndrome is common in the general population, particularly in elderly patients. Antimuscarinic drugs (AMs) are considered the mainstay pharmaceutical treatment of OAB whereas β3-adrenoceptor agonists, such as mirabegron, represent a good alternative. Owing to the important role of muscarinic and β3 receptors in cardiovascular (CV) tissue and to the fact that OAB patients often have CV comorbidities, the safety-profile of these drugs constitute an important challenge. Area covered : The aim of this review is to evaluate the CV effects of AMs and mirabegron in OAB. A systematic literature search from inception until December 2017 was performed on PubMed and Medline. Expert opinion : AMs are generally considered to have good CV safety profile but, however, they may cause undesirable adverse events, such as dry mouth, constipation. CV AEs are rare but noteworthy, the most common CV consequences related to the use of these drugs are constituted by an increase in HR and QT interval. Mirabegron has similar efficacy and tolerability to AMs but causes less adverse events, with either modest hypertension and modest increase in HR (<5 bpm) being the most commonly reported.